New Models and E-Learning Trends in Teacher Education and Professional Development - Wani, Hilal Ahmad (EDUCARE, 2011)
ABSTRACT: With the advent of the knowledge era, teacher education needs to prepare teachers to face the changing technological contexts and to model pedagogies and tools for better forms of learning. Despite much enthusiasm about the roles of technology in education, its role in transforming teacher learning, in ways aligned with advances in the learning sciences and contemporary socio-cultural perspectives, few changes have occurred. While many teacher educators are turning away from technology after early attempts met with mitigated success, some are pushing the boundaries of teacher education and professional activity systems. This paper identifies and analyzes emerging trends and models in e-learning for teacher education and professional development from the developing research base, both international trends and current developments. As we know that globalization cannot be understood without including information and communication technology (ICT). Educational institutions and teaching staff have many benefits due to emergence of modern technology. Teachers have their own networks through which they connect themselves with other teachers across the globe. Institutions have web-supported classrooms. Similarly, it also enhanced the responsibilities of schools, colleges, universities that should have such teachers who can produce such students who after receiving their education can adjust themselves at any platform. KEY WORDS: Teacher education, technology in education, models in e-learning, and teacher professional development.About the Author: Hilal Ahmad Wani is Research Scholar at the Department of Political Science AMU (Aligarh Muslim University), Aligarh, Uttaraparadesh, India. He can be reached at: wanihilal@gmail.comHow to cite this article? Wani, Hilal Ahmad. (2011). âNew Models and E-Learning Trends in Teacher Education and Professional Developmentâ in EDUCARE: International Journal for Educational Studies, Vol.4(1) August, pp.1-10. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 1, 2011); Revised (July 3, 2011); and Published (August 17, 2011).